2021
DOI: 10.3390/plants10112336
|View full text |Cite
|
Sign up to set email alerts
|

Role of Benzoic Acid and Lettucenin A in the Defense Response of Lettuce against Soil-Borne Pathogens

Abstract: Soil-borne pathogens can severely limit plant productivity. Induced defense responses are plant strategies to counteract pathogen-related damage and yield loss. In this study, we hypothesized that benzoic acid and lettucenin A are involved as defense compounds against Rhizoctonia solani and Olpidium virulentus in lettuce. To address this hypothesis, we conducted growth chamber experiments using hydroponics, peat culture substrate and soil culture in pots and minirhizotrons. Benzoic acid was identified as root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…BA has been documented to influence several physiological processes, including anthocyanin production, chlorophyll biosynthesis, ion uptake, root elongation, and enzyme activity ( Maffei et al , 1999 ). Additionally, Windisch et al (2021) showed that lettuce roots secrete benzoic acid as a defensive metabolite against fungal pathogens. Taking all of the above data into account, an explanation for the accumulation of BA in our samples may be that this compound has a defensive role.…”
Section: Resultsmentioning
confidence: 99%
“…BA has been documented to influence several physiological processes, including anthocyanin production, chlorophyll biosynthesis, ion uptake, root elongation, and enzyme activity ( Maffei et al , 1999 ). Additionally, Windisch et al (2021) showed that lettuce roots secrete benzoic acid as a defensive metabolite against fungal pathogens. Taking all of the above data into account, an explanation for the accumulation of BA in our samples may be that this compound has a defensive role.…”
Section: Resultsmentioning
confidence: 99%
“…The main classes of such compounds are represented by phenylpropanoids, flavonoids and phenolic polymers, in particular, lignin [ 7 , 9 , 37 ]. Because of their chemical properties, they readily interact with ROS, thereby protecting cells from their negative effects [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hydroxybenzoic acids, derived from benzoic acid, lead to the synthesis of several other phenolic compounds, including plant hormones, and co-factors [ 78 ], mainly polar, and therefore not detected by the GC-MS. The synthesis of benzoic acid can also be induced by pathogens [ 8 , 79 ].…”
Section: Resultsmentioning
confidence: 99%